2017
DOI: 10.1136/gutjnl-2016-313457
|View full text |Cite
|
Sign up to set email alerts
|

Phase II evaluation of anti-MAdCAM antibody PF-00547659 in the treatment of Crohn’s disease: report of the OPERA study

Abstract: ObjectiveThis phase II, randomised, double-blind, placebo-controlled clinical trial was designed to evaluate the efficacy and safety of PF-00547659, a fully human monoclonal antibody that binds to human mucosal addressin cell adhesion molecule (MAdCAM) to selectively reduce lymphocyte homing to the intestinal tract, in patients with moderate-to-severe Crohn’s disease (CD).DesignEligible adults were aged 18–75 years, with active moderate-to-severe CD (Crohn’s Disease Activity Index (CDAI) 220–450), a history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 27 publications
(25 reference statements)
1
78
0
Order By: Relevance
“…The main limitation is the lack of direct clinical translatability of the particles and antibodies that were used in the present study. However, biodegradable MPIOs are now available( 27 ) and anti-human MAdCAM-1 antibodies are currently under clinical investigation( 28 ), opening the way for clinical translation of our imaging method by coupling the two constructs.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation is the lack of direct clinical translatability of the particles and antibodies that were used in the present study. However, biodegradable MPIOs are now available( 27 ) and anti-human MAdCAM-1 antibodies are currently under clinical investigation( 28 ), opening the way for clinical translation of our imaging method by coupling the two constructs.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 2, parallel, dose‐ranging, randomized, double‐blind, placebo‐controlled clinical trial in patients with moderate to severe CD who had a history of treatment failure, or intolerance to immunosuppressants and/or anti–tumor necrosis factor (TNF) agents was performed (A7281006, ClinicalTrials.gov identifier: NCT01276509; OPERA) 5 . Patients eligible for this study must have met the entry criteria (details of which have been published previously 5 ), which specified a high‐sensitivity C‐reactive protein (CRP) concentration greater than the upper limit of normal (3.0 mg/L). In this study, 3 subcutaneous (SC) dose levels (22.5, 75, and 225 mg) of ontamalimab were compared with placebo (in a 1:1:1:1 ratio).…”
Section: Methodsmentioning
confidence: 99%
“…Patients were randomly assigned to 1 of 4 treatment arms for the 12‐week induction period and stratified by the status of anti‐TNF experience or immunosuppressant intolerance/failure and concomitant immunosuppressant therapy. The primary efficacy end point was the proportion of patients with a decrease in Crohn's Disease Activity Index score of at least 70 points from baseline to week 8 or week 12 5 . A minimum of 240 randomized patients (60 per treatment group) were required to evaluate the primary end point.…”
Section: Methodsmentioning
confidence: 99%
“…134 However, the phase 2 OPERA study in patients with active refractory CD failed to meet its primary end point, despite evidence of target engagement. 135 In the phase 1 safety study, TOSCA, in patients with active CD, 12 weeks of SHP647/ontamalimab induction therapy did not result in a reduction in CSF lymphocytes or T-cell subsets or CD4:CD8 ratio. 136 The data from extension studies for UC (TURNADOT II) and CD (OPERA and TOSCA) demonstrated that efficacy achieved with SHP647/ontamalimab induction were maintained for up to 144 weeks and 72 weeks, respectively.…”
Section: Madcam-1 As a Target For The Treatment Of Ibdmentioning
confidence: 97%
“…In the phase 2 TURANDOT trial in patients with moderate to severe UC, 12 weeks of SHP647/ontamalimab treatment resulted in significantly greater remission rates at 7.5 mg, 22.5 mg, and 75 mg doses every 4 weeks compared with placebo . However, the phase 2 OPERA study in patients with active refractory CD failed to meet its primary end point, despite evidence of target engagement . In the phase 1 safety study, TOSCA, in patients with active CD, 12 weeks of SHP647/ontamalimab induction therapy did not result in a reduction in CSF lymphocytes or T‐cell subsets or CD4:CD8 ratio .…”
Section: A Model For Integrins and T Lymphocytes As Therapeutic Targementioning
confidence: 98%